A matrix-based revision of the genus Hypogena Dejean, 1834 (Coleoptera: Tenebrionidae) - Grey, Luna; Smith, Aaron D. (Zootaxa, 2020)
The darkling beetle genus Hypogena Dejean, 1834 (Tenebrionidae: Tenebrioninae) is revised. Hypogena is entirely composed of dorsoventrally flattened species that live subcortically in dead trees. This genus is generally identified by male specific characters, particularly the presence of cephalic horns. Hypogena is currently placed within the tribe Triboliini Gistel, 1848. However, several previously overlooked morphological characters call into question its placement within the tribe. A morphological matrix of 94 external adult characters was assembled to examine species relationships and boundaries. The resulting phylogeny is presented. Thirteen Hypogena species were previously recognized as valid, including Hypogena marginalis Doyen & Poinar from Dominican amber. Four previously unidentified species are described in this study: Hypogena akuma sp. nov. (Brazil), Hypogena cryptica sp. nov. (Mexico), Hypogena hirsuta sp. nov. (Ecuador), and Hypogena reburra sp. nov. (Colombia). Lectotypes are designated for Hypogena depressa (Champion, 1886), Hypogena dejeani (Champion, 1886), Hypogena canaliculata (Champion, 1886), and Hypogena vacca (Fabricius, 1801). A neotype is designated for Tenebrio biimpressus (Latreille, 1833) (type species of Hypogena, synonymized under Hypogena brasilica (Perty)) in order to maintain stability within the genus.